2013
DOI: 10.1016/j.nbd.2012.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Focal Scn1a knockdown induces cognitive impairment without seizures

Abstract: Cognitive impairment is a common comorbidity in pediatric epilepsy that can severely affect quality of life. In many cases, antiepileptic treatments fail to improve cognition. Therefore, a fundamental question is whether underlying brain abnormalities may contribute to cognitive impairment through mechanisms independent of seizures. Here, we examined the possible effects on cognition of Nav1.1 down-regulation, a sodium channel principally involved in Dravet syndrome but also implicated in other cognitive disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 58 publications
(101 reference statements)
3
55
3
4
Order By: Relevance
“…A study in which Na v 1.1 was down-regulated in the medial septum showed that this led to a disruption in the septohippocampal network with impairments in hippocampal-dependent functions, but in the absence of any seizures. This strongly supports the view that there are direct negative cognitive effects of the mutation and that seizures are not required for cognitive impairment (Bender et al 2013). …”
Section: Genetic Etiologysupporting
confidence: 84%
“…A study in which Na v 1.1 was down-regulated in the medial septum showed that this led to a disruption in the septohippocampal network with impairments in hippocampal-dependent functions, but in the absence of any seizures. This strongly supports the view that there are direct negative cognitive effects of the mutation and that seizures are not required for cognitive impairment (Bender et al 2013). …”
Section: Genetic Etiologysupporting
confidence: 84%
“…In contrast, SCN1A deletion within excitatory neurons of the forebrain does not produce epilepsy . This is further supported by the observation that focal deletion of SCN1A in basal forebrain neurons does not result in epilepsy, but causes dysregulation of hippocampal oscillations and spatial memory deficit (Bender et al 2013). Even more interestingly, combined deletion in both inhibitory and forebrain excitatory neurons ameliorates the seizure-related sudden death expected from the interneuronal CKO .…”
Section: Animal Models Of Early-life Epilepsymentioning
confidence: 71%
“…Comorbidities of Refractory Epilepsy decreased excitability of GABAergic cerebellar Purkinje cells caused by SCN1A mutation not only contributes to seizure but also can be linked with learning and behavioral dysfunction [30]. Epilepsy and cognitive comorbidities attribute to interictal frequent epileptiform discharges, which impair synaptic plasticity, neurogenesis and memory retrieval by inhibition of action potential firing through spine loss in pyramidal cells in hippocampal CA3 [31].…”
Section: Reviewmentioning
confidence: 99%